Meningkatkan Pemahaman Konsep Berhitung 1-10 melalui Gambar Menarik Kelas 1.A UPT SPF SD Inpres Mallengkeri II - Ardiyanti Ardiyanti; A L Arika Maya Sari; Dendy Setyo Anggoro (Departement of Mathematics Education, 2024)
This study aims to improve the understanding of the concept of counting 1-10 in class 1.A students of UPT SPF SD Inpres Mallengkeri II through the use of interesting pictures. This study uses a classroom action research (CAR) design consisting of two cycles, namely cycle 1 and cycle 2. The subjects of this Classroom Action research were 28 students of class 1.A UPT SPF SD Inpres Mallengkeri II. The data collection technique used in this study was the Test and Observation Technique, then the data obtained from the analysis was analyzed to determine whether through interesting picture media it could improve students' understanding of the concept of counting 1-10. Based on the results of the analysis and data management carried out by researchers in cycles 1 and 2, it can be found that the results of the study showed a significant increase in students' understanding after the application of this method. In cycle 1, only 75% of students achieved completeness, while in cycle 2, students' completeness increased to 89%. The use of interesting pictures helps students visualize the concept of counting, which contributes to improving their understanding.